Degradation of gaseous VOCs by advanced oxidation processes UV-assisted ozonation and ultrasonication - Comia, Jose R. Jr.; Ballesteros, Florencio C. Jr.; Naddeo, Vincenzo (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Volatile organic compound (VOC) emissions have become a key air pollution concern due to adverse health and environmental effects. The refractory nature of organic compounds combined with the toxicity of secondary metabolites limit the physical chemical treatment processes and conventional biological processes. To overcome these drawbacks, the development of innovative advanced oxidation processes (AOPs) for the degradation of gaseous organic compounds is of major interest. This work presents the results of two AOPs in the degradation of gaseous VOCs (toluene as a representative compound) - UV irradiation with ozonation (UV/O3) and ultrasonication (US) - considering various operating parameters such as initial toluene concentration, ozone dosage, and ultrasound frequency. For the UV/O3 process, increase in inlet concentration resulted to a decrease in toluene removal while increase in ozone dosage lead to a higher removal. An additional water scrubbing step for the UV/O3 process enhanced the abatement up to 99% due to solubilization of ozone and further oxidation of contaminants. For the US process, increase in inlet concentration had varying effects at different frequencies. Increase in US frequency and additional water recirculation lead to an increase in the removal efficiency. However, addition of ozone proved to be inhibitory for the process. In comparison, UV/O3 proved to be more efficient in terms of toluene removal at lower inlet load while US resulted to higher elimination at higher loading.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Volatile organic compounds -- Biodegradation